Proposta de aplicação de ferramentas de business intelligence e de business process management na gestão da informação nos almoxarifados dos centros acadêmicos da UFRN - Gomes, Liliane Leopoldina de Medeiros (2023)
Information is an intangible asset of great value to organizations and its management has become indispensable for generating competitive advantage, both in the private and public spheres. However, the excessive amount of information makes its management complex, mainly for the creation of knowledge and, consequently, for intelligence. As it is present in any company action, information is inherent to organizational processes. Thus, the alignment of information management with process management is an increasingly common practice. In this context, the joint use of tools such as Business Intelligence (BI) and Business Process Management (BPM) can contribute to efficient organizational management. Given the above, the present study aims to propose a Business Intelligence solution aligned with a standardization of processes, through Business Process Management, to optimize the use of materials available in the warehouses of the academic centers of the Federal University of Rio Grande do Sul. North, based on the assertiveness of information flows. The methodological course used was based on the inductive approach method and the methods of monographic and comparative procedure. The research is characterized as mixed, as quantitative and qualitative collection instruments were used. Thus, mixed-type questionnaires were used, with open and closed questions, which were applied to the coordinators of each warehouse. Semi-structured interviews were also carried out with these actors and aimed to obtain information for mapping processes through flowcharts. In the data analysis, descriptive statistics were used for the closed questions of the questionnaires, and the results were presented in tables and graphs. As for the open questions and semi-structured interviews, the qualitative data analysis process was used, as well as data triangulation. From the results obtained, it was possible to identify the actions that result in the inefficient use of the institution's materials, such as the lack of information sharing between the managers of the warehouses studied, referring to the materials available at the university. It was also identified the lack of records of essential information for the efficient management of stocks. In this way, a Business Intelligence solution was developed, through Power BI, as a proposal for a complementary tool to the system already used in the institution, for the management of information, as well as for its sharing. A standardized flow of process information was also prepared through Business Process Management, aiming to guide warehouse managers on the steps to be followed in the processes inherent to the sector, aiming at the efficiency in the use of these tools for the best use of university inputs.